Profiling Needs of X Private University's Students in Jakarta Using McClelland's Theory Approach - Nindyati, Ayu Dwi (Universitas Nusa Cendana, 2023)
Most students want a job after college, and the desire arises from the needs that move humans to do something. This study uses the quantitative-descriptive method to determine the need profile based on McClelland’s Theory in X Private University’s students in Jakarta. Participants in this study (N=139) were students aged 18-41 years and spread across 12 study programs. The data obtained is analysed using compare means technique to see the average needs based on groups of respondents. The results show that overall, the profile of the needs found was dominated in order by need for affiliation, need for achievement, and need for power. This finding can use to make an appropriate intervention according to the dominance of needs in students to increase student motivation in exploring their abilities.